Animal spirits, technology shocks and the business cycle - Mark Weder (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
In this paper a two-sector growth model allowing indeterminacy to occur at relatively mild degrees of increasing returns is developed. It is shown that these economies of scale need only be present in one sector of the economy (investment). This feature of the model, therefore, builds on evidence that was recently reported by Basu and Fernald (1996). The model is also able to solve some puzzles of business cycle research which standard Real Business Cycle models have not been able to. The introduction of animal spirits generates a low negative contemporaneous correlation of hours and productivity as well as a procyclical investment share. The model can account for the observed variability of hours worked.
urn:nbn:de:kobv:11-10064504
Keywords: E00; E32; 330; Sunspots; technology shocks; economic fluctuations; Dunlop-Tarshis-puzzle